Space Radiation Alters Genotype–Phenotype Correlations in Fear Learning and Memory Tests - Iancu, Ovidiu Dan; Boutros, Sydney Weber; Olsen, Reid H. J.; Davis, Matthew J.; Stewart, Blair; Eiwaz, Massarra; Marzulla, Tessa; Belknap, John; Fallgren, Christina M.; Edmondson, Elijah F.; Weil, Michael M.; Raber, Jacob (Frontiers in Genetics, 2018)
Behavioral and cognitive traits have a genetic component even though contributions from individual genes and genomic loci are in many cases modest. Changes in the environment can alter genotype-phenotype relationships. Space travel, which includes exposure to ionizing radiation, constitutes environmental challenges and is expected to induce not only dramatic behavioral and cognitive changes but also has the potential to induce physical DNA damage. In this study, we utilized a genetically heterogeneous mouse model, dense genotype data, and shifting environmental challenges, including ionizing radiation exposure, to explore and quantify the size and stability of the genetic component of fear learning and memory-related measures. Exposure to ionizing radiation and other external stressors altered the genotype-phenotype correlations, although different behavioral and cognitive measures were affected to different extents. Utilizing an integrative genomic approach, we identified pathways and functional ontology categories associated with these behavioral and cognitive measures.